Comparative Analysis of Database Query Storage Performance Between Stored Procedure and Function - Abednego Dwi Septiadi; Lee Jeong Bae (International Journal of Informatics and Information Systems, 2020)
This research was conducted to measure the data storage time carried out by the DBMS on data that has been prepared with an increasing number of data, the data provided is consistent student data which will be stored with Stored Procedure and Function. This study uses the action research method which has 4 stages, starting with planning, action, observation and reflection. From the results of the experiments that have been carried out, it appears that Stored Procedure is able to outperform Function in data storage time. The data provided are 2 different types of data, each of which consists of 500, 2500, 4500 and 6500 data stages. This study also compares data storage that is differentiated by the computer between the data provider computer and the data storage computer or server, the result of which is the Stored Procedure. able to outperform Function in data storage speed.